Antibiotics Resistant and Genetic Diversity of Escherichia coli Isolated From Aquaculture Environments - Nurismi, Ismaili (Universiti Malaysia Sarawak, UNIMAS, 2013)
The use of antibiotics in the aquaculture environments poses a risk that resistance to antibiotics will develop in the environmental organisms, in the endogenous bacterial population of farmed species, and in their pathogens. Antibiotic resistance bacteria constitute direct or indirect threat to farmers and the public through potential transfer of resistance to human and animal pathogens. This study was conducted to obtain a preliminary indication of the extent of antibiotic resistance in the aquaculture environments in Sarawak. Escherichia coli were isolated from the fish, water, and the sediment of the aquaculture environments. Antibiotic susceptibility test was conducted to determine the antibiotic resistance patterns of the isolates. DNA profiling of E. coli was conducted to see the diversity of the isolates in the aquaculture environment through RAPD-PCR analysis. Nineteen isolates of E. coli were isolated from the fish, water and sediment. All the isolates show resistant to at least one of the eight antibiotics tested. The highest level of resistance was observed against erythromycin (94.74%) and the lowest was against nalidixic acid (5.26%). The RAPD analysis with primers Gen-1-50-09 and Gen1-50-10 grouped the E. coli isolates in 4 and 3 main groups, respectively. The results of this study suggested that E. coli isolates were genetically diverse and the fish, sediment and water are potential reservoir for antibiotic resistance of E. coli.